Due Process and the Reconstruction of Democracy - Martinot, Steve (Social justice, 2016)
This article attempts to rescue the concept of due process from the limited field of legal procedure to look instead at its political potential as well as the effects of its denial. I argue that due process as a principle is at the core of any concept of democracy and that its withholding is already a signifier for autocracy. This has important implications in several domains, including the housing crisis and police brutality.